Is an interval the right result of arithmetic operations on intervals? - Piegat, Andrzej; Landowski, Marek (Zielona Góra: Uniwersytet Zielonogórski)
For many scientists interval arithmetic (IA, I arithmetic) seems to be easy and simple. However, this is not true. Interval arithmetic is complicated. This is confirmed by the fact that, for years, new, alternative versions of this arithmetic have been created and published. These new versions tried to remove shortcomings and weaknesses of previously proposed options of the arithmetic, which decreased the prestige not only of interval arithmetic itself, but also of fuzzy arithmetic, which, to a great extent, is based on it.
Keywords: interval arithmetic; one-dimensional interval arithmetic; multi-dimensional interval arithmetic; RDM interval arithmetic